The Essence of the Islamic Education Curriculum as a Foundation for Islamic Learning - Sumarni, Sumarni; Atjo, Andi Sukmawati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
The Islamic education curriculum plays a crucial role in shaping a generation with noble character, faith, and a balance between knowledge, attitudes, and skills. This article discusses the role of the Islamic education curriculum in building students' character through the instillation of Islamic values ​​derived from the Qur'an and Hadith. The Islamic education curriculum focuses not only on academic aspects but also emphasizes the moral, spiritual, and social development of students so they can face the changing times without losing their Islamic identity. The method used in writing this article is a literature study by analyzing various sources of literature related to the Islamic education curriculum and moral formation. The results of the discussion indicate that the implementation of an integrated Islamic education curriculum can shape individuals who are disciplined, responsible, tolerant, and have noble character. Therefore, the development of the Islamic education curriculum needs to be carried out continuously to remain relevant to the needs of modern society and to produce a generation that excels intellectually and spiritually.